PSYCHOLOGICAL AND PEDAGOGICAL FOUNDATIONS OF DESIGN IN FINE ARTS EDUCATION (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This article examines the psychological and pedagogical foundations of design in fine arts education. Through design elements, the processes of forming students' artistic and aesthetic thinking, creative abilities, and practical skills are analyzed. The psychological characteristics of students and the importance of pedagogical approaches appropriate to the age period are also highlighted. As a result of observations conducted on the basis of an integrated approach, the motivational, cognitive, and creative developmental functions of design in the educational process were determined.